Pareto: A View of the Present through the Past - Tarascio, Vincent J. (Journal of Political Economy, 1976)
This paper examines those factors which caused Pareto to change his philosophical views with age and the effect of these changes on the man and his work. The approach is essentially biographical. Finally, the present state of economics is viewed in the context of the historical background of the paper in order to provide a perspective often lacking among economists because of their preoccupation with the present.